International Experience and the Possibilities of the Uzbek Language in Creating Terms (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article explores the problem of term creation by analyzing the international experience of terminology formation and its relation to the internal resources of the Uzbek language. Terminology, as a fundamental element of scientific and technical communication, plays a crucial role in ensuring mutual understanding between specialists at the global and national levels. The study examines how international practices in term creation — borrowing, calquing, semantic extension, and hybridization — interact with the lexical, morphological, and derivational capacities of the Uzbek language. Special attention is paid to the challenges of standardization, the need for cultural adaptation of borrowed terms, and the strategies to maintain both scientific precision and linguistic authenticity. Based on the analysis of international experience and the internal linguistic potential of Uzbek, recommendations are made for the effective development of modern Uzbek terminology, especially in the fields of science, technology, and socio-political discourse.